Ascomycetes (Fungi) from the relic forest of Fagus grandifolia subsp. mexicana in eastern Mexico - Raymundo, Tania; Valenzuela, Ricardo; García-Martínez, Yenitze; Bravo-Álvarez, Marco Antonio; Ramírez-Martínez, Julio César; Bautista-Hernández, Silvia; Palacios-Pacheco, Mauricio; Luna-Vega, Isolda (Phytotaxa, 2019)
An intensive recollection of Ascomycetes was carried out within the best-known preserved Mexican tropical montane cloud forest patch dominated by Fagus grandifolia subsp. mexicana. This relict tree species has a fragmented and restricted distribution in the mountains of eastern Mexico. Other Mexican endemic Fagaceae species show dominance in this forest patch. Historically, records of Ascomycetes fungi in this type of forest are scarce. The present study found 170 specimens belonging to 61 species, of which 30 are new records for the state, while 10 species are cited for the first time in the country. Most of the recorded Ascomycetes species are intimately associated to Fagaceae tree species (Fagus and Quercus). From these, many are endophytes belonging to the Order Xylariales, while others grow on decaying wood, fallen branches, leaves and/or litter (possibly mycorrhizal). This interesting close relationship between fungi and Fagaceae trees must be studied and analyzed.